Local electrical conductivity of carbon black/PDMS nanocomposites subjected to large deformations. (February 2023) - Moronkeji, Oluwadara E; Das, Debashish; Lee, Sunho; Chang, Kelly M; Chasiotis, Ioannis
The full-field microscale electrical behavior of polydimethylsiloxane (PDMS) matrix composites with 12 wt% (below the electrical percolation threshold) and 20 wt% (above the electrical percolation threshold) carbon black (CB) nanoparticles was obtained with the aid of Conductive Atomic Force Microscopy (C-AFM) as a function of uniaxial tensile strain. A comparison between the macroscale and the microscale 2D strain fields showed that 25 × 25 μm 2 specimen domains can serve as a representative surface element (RSE) to describe the macroscale mechanical response under finite deformations. The same surface domain size was shown to serve as RSE for the local electrical behavior of CB/PDMS nanocomposites at small and large strains. The transverse specimen contraction due to the Poisson's effect increased the through-thickness conductivity of 12 wt% CB specimens, with a rapid increase in the total electric current measured at the scale of the RSE taking place above 23% uniaxial true strain. The locally dominant tunneling conductance in the undeformed specimen state transitioned to a combination of Ohmic (linear local current-voltage (I–V) characteristics) and tunneling (parabolic local I–V characteristics) at 35% uniaxial true strain. In comparison, the local I–V characteristics of undeformed PDMS composites with 20 wt% CB were a combination of Ohmic (contributing the majority of the total current) and tunneling. Upon application of 35% uniaxial true strain the vast majority of local conduction sites became Ohmic, while the total electric current at the scale of the RSE increased relatively linearly with applied strain.